Combined effects of livestock grazing and abiotic environment on vegetation and soils of grasslands across Tibet. Issue 3 (30th May 2017) - Wang, Yun; Heberling, Gwendolyn; Görzen, Eugen; Miehe, Georg; Seeber, Elke; Wesche, Karsten
Abstract: Questions: Livestock grazing and abiotic environmental factors both shape grassland systems; however, the relative importance of their impacts on plant species composition and soil fertility has rarely been investigated. Focusing on Tibetan grasslands, which are of global ecological importance and exhibit broad climatic and elevational gradients, we asked whether grazing effects are pronounced in humid regions, while climate controls are overriding grazing effects in semi‐arid regions. Location: Twenty‐eight sites across Tibetan pastures, China; 2820–5150 m a.s.l. Methods: We used multivariate analyses and generalized linear mixed models to examine the effects of livestock activity (hotspots with excessive trampling and nutrient input, heavy, moderate and light grazing), habitat (meadow, steppe, steppe‐meadow) and their interactions. We focused on plant species composition, richness and concentrations of soil organic carbon (SOC), total N and other plant‐available nutrients in soils. Major environmental factors were precipitation, temperature and elevation. Plant indicator species sensitive to trampling and/or grazing were identified. Results: Livestock grazing changed plant species composition and overall soil fertility across habitats. However, effects were only pronounced in hotspots directly adjacent to herder camps, while differences between grazing intensity levels were weak. Heavy grazing favoured annual species, reduced concentrations of SOC and total N in meadows. The environmental factors that control plant communities and soil condition varied among habitats. Plants and soils were more tightly linked in steppes and steppe‐meadows than in meadows. Conclusions: Several plant species were identified as frequently and reliably present in hotspots of livestock activity, thus are indicative of intensive trampling and excess plant available nutrient inputs. Overall, plant species composition and soil condition across Tibetan pastures were weakly affected by intensified grazing alone compared to that shaped by environmental factors. This clearly refutes the broadly held perception that increased grazing intensity leads to grassland degradation. Such differing and strong abiotic impacts should be considered in future grassland management and conservation. Abstract : Effects of livestock‐grazing on plant communities and soil conditions were assessed at 28 sites spreading across Tibetan pastures, covering all major habitats. Grazing effects were pronounced at hotspots with heavy livestock trampling and nutrient inputs, while differences between light and intensive grazing were limited. Effects of climatic controls were very strong, and thus must be considered in future grassland management.